Stressful life events and maltreatment in conversion (functional neurological) disorder: systematic review and meta-analysis of case-control studies. (April 2018) - Ludwig, Lea; Pasman, Joëlle A; Nicholson, Timothy; Aybek, Selma; David, Anthony S; Tuck, Sharon; Kanaan, Richard A; Roelofs, Karin; Carson, Alan; Stone, Jon
Summary: Background: Stressful life events and maltreatment have traditionally been considered crucial in the development of conversion (functional neurological) disorder, but the evidence underpinning this association is not clear. We aimed to assess the association between stressors and functional neurological disorder. Methods: We systematically reviewed controlled studies reporting stressors occurring in childhood or adulthood, such as stressful life events and maltreatment (including sexual, physical abuse, and emotional neglect) and functional neurological disorder. We did a meta-analysis, with assessments of methodology, sources of bias, and sensitivity analyses. Findings: 34 case-control studies, with 1405 patients, were eligible. Studies were of moderate-to-low quality. The frequency of childhood and adulthood stressors was increased in cases compared with controls. Odds ratios (OR) were higher for emotional neglect in childhood (49% for cases vs 20% for controls; OR 5·6, 95% CI 2·4–13·1) compared with sexual abuse (24% vs 10%; 3·3, 2·2–4·8) or physical abuse (30% vs 12%; 3·9, 2·2–7·2). An association with stressful life events preceding onset (OR 2·8, 95% CI 1·4–6·0) was stronger in studies with better methods (interviews; 4·3, 1·4–13·2). Heterogeneity was significant between studies ( I 2 21·1–90·7%). 13 studies that specifically ascertained that the participants had not had either severe life events or any subtype of maltreatment all found a proportion of patients with functional neurological disorder reporting no stressor. Interpretation: Stressful life events and maltreatment are substantially more common in people with functional neurological disorder than in healthy controls and patient controls. Emotional neglect had a higher risk than traditionally emphasised sexual and physical abuse, but many cases report no stressors. This outcome supports changes to diagnostic criteria in DSM-5; stressors, although relevant to the cause in many patients, are not a core diagnostic feature. This result has implications for ICD-11. Funding: None.